Autonomie, vitalité et identité des communautés en situation minoritaire : proposition d’un cadre conceptuel - Forgues, Éric (Revue internationale d’études canadiennes, 2010)
Quels facteurs contribuent à la vitalité linguistique d’une communauté en situation minoritaire et lui assurent les conditions propres à favoriser sa reproduction linguistique et culturelle? Nous nous proposons de présenter un modèle conceptuel susceptible de répondre à cette question. Selon ce modèle, trois facteurs sont au fondement de la reproduction linguistique d’une communauté en situation minoritaire : la gouvernance, l’identité et la vitalité, avec comme point pivot, la société civile et l’espace public. Cet article présente non seulement la fonction de ces facteurs au sein des communautés, mais les sous-fonctions qui découlent de leurs interrelations, tels que la lutte pour la reconnaissance, le droit, la complétude institutionnelle, l’engagement social et l’expression identitaire publique et privée. Ce modèle peut être utile pour saisir, d’un point de vue global, les composantes de la reproduction des communautés en situation minoritaire, pour déterminer celles qui la compromettent et, ainsi, envisager des pistes d’action.

L'environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, A.; Langlois, A.; Landry, R.; Aunger, A. E. (Territoires francophones : études géographiques sur la vitalité des communautés francophones du Canada, 2010)
fs-ref-orig: Gilbert, A., Langlois, A., Landry, R. et Aunger, A. E. (2010). L'environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel. Dans A. Gilbert (dir.), Territoires francophones : études géographiques sur la vitalité des communautés francophones du Canada (chap. 1). Les Éditions du Septentrion. fs-code-orig: Gilbert-2010a Chapitre: 1

Participation citoyenne, francophonie minoritaire et gouvernance des services de santé : les conceptions des acteurs - Lévesque, Maurice; Burlone, Nathalie; Boyer, Émilie (Université d'Ottawa, 2010)

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.